Raman spectral identification of phase distribution in anodic titanium dioxide coating - Knoks, Ainars; Kleperis, Janis; Grinberga, Liga (Estonian Academy of Sciences, 2017)
Growing need for cleaner environment and energy production has brought about a hunt for perspective materials. One of such perspective materials is titanium dioxide (TiO2, titania) due to its chemical stability and photocatalytic properties. Titania can be synthesized through many methods but anodization process is one of the prevailing methods to produce high active surface nanostructured titania. Various anodization electrolytes produce different polymorphs of TiO2. Uniform phase distribution on the surface is crucial for higher photocatalytic activity. In this research, the influence of two electrolytes on polymorph phase distribution of TiO2 was investigated. Phase distribution correlation with optical band gap, charge density and photocurrent values were tested. Successful Raman investigation of anodized titania revealed uniform, single and multi-phase, as well as nonuniform phase distributions produced respectively in PO43‒ and SO42‒ ions containing electrolytes. Uniform single phase titania shows highest photocurrent (PCR) and charge density values compared to phase composition and nonuniform phase distributions. We have shown Raman microprobe analysis as indispensable method for wholesome sample characteristics.
Keywords: TiO2; Structure; anodization; Raman; Research Subject Categories::NATURAL SCIENCES::Physics